Modulation of Gap Junction Coupling Within the Islet of Langerhans During the Development of Type 1 Diabetes - Farnsworth, Nikki L.; Piscopio, Robert A.; Schleicher, Wolfgang E.; Ramirez, David G.; Miranda, Jose G.; Benninger, Richard K. P. (Frontiers in Physiology, 2022)
In type 1 diabetes (T1D), islet dysfunction occurs prior to diabetes onset. Pro-inflammatory cytokines can disrupt insulin secretion and Ca2+ homeostasis. Connexin36 (Cx36) gap junctions electrically couple -cells to coordinate glucose-stimulated Ca2+ and insulin secretion. Cx36 gap junction coupling can also protect against cytokine-induced apoptosis. Our goal was to determine how islet gap junction coupling and Ca2+ dynamics are altered in mouse models of T1D prior to diabetes. Glucose tolerance was assessed in NOD and immunodeficient NOD-RAG1KO mice at 6-12 weeks age. Glucose-stimulated insulin secretion, Ca2+ dynamics, and gap junction coupling were measured in islets isolated at each age. Gap junction coupling was also measured in islets from mice that underwent transfer of diabetogenic splenocytes and from chromograninA knockout NOD mice. Cell death was measured in islets isolated from wild-type, Cx36 knockout or Cx36 over-expression mice, each treated with a cocktail of pro-inflammatory cytokines and KATP or SERCA activators/inhibitors. NOD mice over-expressing Cx36 were also monitored for diabetes development, and islets assessed for insulitis and apoptosis. NOD and NOD-RAG1KO controls showed similar glucose tolerance at all ages. Ca2+ dynamics and gap junction coupling were disrupted in islets of NOD mice at 9 weeks, compared to controls. Transfer of diabetogenic splenocytes also decreased gap junction coupling. Islets from chromograninA knockout mice displayed normal coupling. Overexpression of Cx36 protected islets from cytokine-induced apoptosis. A knockout of Cx36 amplified cytokine-induced apoptosis, which was reversed by KATP activation or SERCA activation. Cx36 overexpression in NOD mice delayed diabetes development compared to NOD controls. However, apoptosis and insulitis were not improved. Decreases in islet gap junction coupling occur prior to T1D onset. Such decreases alter islet susceptibility to apoptosis due to altered Ca2+. Future studies will determine if increasing Cx36 gap junction coupling in combination with restoring Ca2+ homeostasis protects against islet decline in T1D.